655 Scoliotic postural alignment in prepubertal children: somatoscopic analysis of anatomical landmarks and development of a working model to limit spinal changes (Balneo and PRM Research Journal, 2024)
The study aims to perform a somatoscopic analysis on a sample of 100 prepubertal children aged 10-14 years, girls and boys, who are diagnosed with scoliosis. Somatoscopic assessment is one of the most commonly used, therefore we thought that making a way of interpreting the results could be useful to monitor postural attitude in children diagnosed with scoliosis. Identifying the early onset of physical impairment in the spine with somatoscopy can be a key factor in maintaining optimal postural status. This approach may help in achieving a way of working that limits the negative effects of scoliosis on the subjects.  Materials and methods. The selection of subjects is based on exclusion and inclusion criteria related to age, comorbidities, therapeutic approach, and other criteria. Also, aspects that accompany the growth and development process of children in this prepubertal period and factors that may disturb this process are described in detail. Also in this context, we will present basic notions of body posture and etiopathogenesis of the onset of scoliotic deficiencies in children during this period of growth and development. Somatoscopic analysis is performed in the orthostatic position and is based on the identification of anatomical landmarks of the body concerning body posture. Results. From the total analyzed scoliosis, n = 100, 74% are type „C” scoliosis and only 26% are type „S” and in terms of gender, 59% are girls and 41% boys; type „C1” (Cobb angle